2020
DOI: 10.1002/dta.2916
|View full text |Cite
|
Sign up to set email alerts
|

Identification of creatine kinase and alpha‐1 antitrypsin as protein targets of alkylation by sulfur mustard

Abstract: Sulfur mustard (SM) is a toxic chemical warfare agent deployed in several conflicts within the last 100 years and still represents a threat in terroristic attacks and warfare. SM research focuses on understanding the pathophysiology of SM and identifying novel biomarkers of exposure. SM is known to alkylate nucleophilic moieties of endogenous proteins, for example, free thiol groups of cysteine residues. The two‐dimensional‐thiol‐differences in gel electrophoresis (2D‐thiol‐DIGE) technique is an initial proteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 71 publications
2
21
0
Order By: Relevance
“…Based on the positive Western blot results, rat skin was exposed to 12.7 mg SM (10 µL of neat SM applied on a surface of approximately 50 mm 2 ) ex vivo and analyzed for HETE-CK adduct formation. As reported previously by our group, SM alkylates the reactive Cys 282 residue in human CK (Lüling et al 2020). However, after lysis of SM-exposed rat skin samples and direct subsequent proteolysis with ProtK and analysis by µLC-ESI MS/HRMS the expected alkylated CK-derived tetrapeptide TC(-HETE)PS was not detected.…”
Section: Detection Of Ck Alkylation In Rat Skin Ex Vivosupporting
confidence: 60%
See 2 more Smart Citations
“…Based on the positive Western blot results, rat skin was exposed to 12.7 mg SM (10 µL of neat SM applied on a surface of approximately 50 mm 2 ) ex vivo and analyzed for HETE-CK adduct formation. As reported previously by our group, SM alkylates the reactive Cys 282 residue in human CK (Lüling et al 2020). However, after lysis of SM-exposed rat skin samples and direct subsequent proteolysis with ProtK and analysis by µLC-ESI MS/HRMS the expected alkylated CK-derived tetrapeptide TC(-HETE)PS was not detected.…”
Section: Detection Of Ck Alkylation In Rat Skin Ex Vivosupporting
confidence: 60%
“…2a, b). Product ions detected were the same as already described and assigned recently (Lüling et al 2020). Corresponding analysis of blank rat skin not exposed to SM did not show any interferences (Fig.…”
Section: Detection Of Ck Alkylation In Rat Skin Ex Vivosupporting
confidence: 57%
See 1 more Smart Citation
“…Alignment of rmCK and hmCK using the Clustal Omega program (Sievers et al 2011) revealed an overall identity of the amino acid sequences of 96.6% with a complete matching of all Cys and Met positions. Cys 283 was recently identified as a target of alkylating agents including SM (Lüling et al 2021;Steinritz et al 2021). As Cys 283 in the active site of CK (Wang et al 2006) is supposed to bind creatine by electrostatic interactions between the free thiol-moiety of its side chain and the guanidine-group of creatine (Bong et al 2008), we assumed that a loss of CK activity is due to the alkylation of this residue after treatment with SM.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that alkylation of CK with iodoacetamide (IAA) or iodomethane, which both target free Cys residues, reduced the enzyme activity (Atherton et al 1970;Reddy and Watts 1978). Treatment of CK with the alkylating chemical warfare agent sulfur mustard (SM) resulted in the formation of the specific hydroxyethylthioethyl-(HETE)-moiety at Cys 283 (Lüling et al 2021;Steinritz et al 2021) but its effect on enzyme activity has not been addressed so far. This was investigated in the present study with particular focus on Cys 283 but also on reactive Met residues, that in principle might also be essential for the activity of certain enzymes (Rogers et al 1976) and were shown to be a potential target of alkylation by SM (Siegert et al 2019).…”
Section: Introductionmentioning
confidence: 99%